Laparoscopic-Assisted Abdominal Wall Pexy of Peritoneal Dialysis Catheter. Issue 1 (January 2021) - Wei, Wei; Fanous, Medhat
Background: Peritoneal dialysis (PD) for rural patients with end-stage renal disease (ESRD) is convenient, efficient, and durable. However, patients with a history of previous abdominal surgeries or peritonitis are at an increased risk of PD malfunction. This case highlights the impact of securing the catheter to the abdominal wall laparoscopically to keep the PD catheter in an adhesion-free area to maintain patency and function in a patient with extensive intraperitoneal adhesions. Subject: A 76-year-old white male was on PD which later was complicated with peritonitis and sepsis and subsequent catheter removal. A year later, the patient desired replacement of the PD catheter. Intraoperatively, diagnostic laparoscopy revealed significant intraperitoneal adhesions mainly located at the left side of the abdomen with the right side of the abdomen spared. The Tenckhoff PD catheter, which was straightened by a steel stylet, was inserted via a 5-mm trocar. The stylet was removed. The pig tail of the PD catheter was navigated away from the adhesion and directed to the right side of the abdomen for internal fixation. The catheter at 9 cm from the PD catheter cuff was attached to the right paramedian peritoneum. Results: PD started 1 week after placement. The patient had excellent inflow and outflow for 14 months to date without complication or need for revision. Conclusion: The laparoscopic pexy of the PD catheter to the abdominal wall to keep the catheter in an adhesion-free compartment is beneficial in selected patients. A future study with a larger number of patients is needed to further validate this strategy.